Factors of Household Agricultural Activity in Russia - Яна Михайловна Рощина; Анна Сергеевна Сухова (Journal of Economic Sociology, 2010)
The theoretical background of the research is an economic sociology approach toward the analysis of private household agricultural activity. On the basis of Russian Longitudinal Monitoring Survey (1994–2006 years) the dynamic of household agricultural activity is examined, the typological analysis of agricultural specialization is carried out; factors that have an impact on household probability to work on their land plots and to put the products of this activity to sale are reviewed.